(untitled) (International Conference on Computers in Education, 2020)
In programming classes, teachers and teaching assistants (TAs) cooperate to support learners’ programming exercises. In many situations while providing support, however, teachers cannot find and resolve the impasse for individual learners while at the same time monitoring the impasse trend in the entire class to effectively provide learners with additional information. In this paper, we categorized 3-level tutoring support information for teachers’ activities and designed the experimental architecture for a system that supports automated extraction for the 3-level information from learners in programming exercise activities.